Social security law and policy reform in Tanzania with reflections on the south African experience. - ACKSON_T (Department of Commercial Law, 2024)
Social security provisioning in Tanzania is grossly inadequate. This is true when one considers the fact that social security schemes, disappointingly, cover less than 6 per cent ofthe total labour force and offer unacceptably low levels of benefits. Other issues are the lack of coordination between the fragmented social security schemes and across countries, and the non-observance of good governance principles in the administration of social security schemes. The aim of this study was to investigate these problems by adopting a human rights approach, of which the South African Constitution of 1996 serves a credible example. South Africa has constitutionalised socio-economic rights, on the basis of which the right to social security is justiciable in the courts of law. The Tanzanian Constitution of 1977, on the other hand, merely considers social security as one of the directive principles of social policy, which are not enforceable in the courts. South Africa has been used as a point of reference for a number of recommendations made in this study, including that Tanzania should consider constitutionalising social security rights in order to deal with the problems identified. In relation to the problems stated above, the study tried to answer the following questions: whether the current social security system provides adequate coverage for the people it purports to cover and whether the social security benefits are adequate. Other questions included the issues of uncoordinated social security schemes in the country and across borders, and the non-transferability of social security benefits. The findings of this study show that social security law in Tanzania is inadequate and unable to fulfil the primary purpose of social protection, that is to say, the protection of the population from the social risks which may befall them and which make them unable to provide for their needs. This is because, firstly, the number of people covered by the existing schemes is very low as the Tanzanian social security system follows the (International Labour Organisation's) formal employment-based social security approach. In this respect, it is recommended that extension of coverage should be prioritised and that this should preferably be done through the establishment of specialised schemes for the excluded groups instead of expanding the scope of the current schemes which were initially tailored to cover formal sector employees. Secondly, social security benefits offered by the existing social security schemes in Tanzania are inadequate, both in terms of numbers and quantum. While the number of benefits offered is informed by the narrow list of the ILO Convention on Social Security (Minimum Standards) of 1952, the low levels of benefits are caused by lack of indexation of benefits in payment, and the deficient use of solidarity principles such as income redistribution and intragenerational and intergenerational equity. The study recommends clear recognition of these factors if adequacy of benefits is to be guaranteed in social security provisioning. Besides this, the study emphasises the need to ensure that good governance principles are incorporated in social security law. A number of recommendations have been made. These include the fact that there is need for the extension of coverage to the excluded, provision of adequate social security benefits to those who are covered, amalgamation of and/or coordination between the fragmented social security schemes and the adoption of good governance principles, which would embrace the participation of stakeholders in decision making, and would ensure transparency and accountability in the administration of social security